Gerakan Revivalis Islam Dan Pembentukan Negara Pakistan Prespektif Ideologi Dan Identitas Nasional - Surya Adi Nugraha; Winda Zahirotus Sa’idah; Dafa Rizqi Ramadhani; Muhammad Ichsanul Irsyad; Umar Al Faruq (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
This abstract discusses the close relationship between the Islamic Revivalist Movement and the formation of Pakistan. The focus of this journal is on the influence of the ideology and national identity shaped by this movement on Pakistan's independence process. The journal analyzes how the "Two Nations" ideology became a primary driver for the demand for a separate state for Muslims in India. The national identity of Pakistan, based on Islamic values, serves as the foundation for the country's legal, educational, and social systems. The aim of this journal is to explore the Islamic Revivalist Movement and the formation of Pakistan from the perspectives of ideology and national identity. It examines how the Islamic Revivalist Movement shaped Pakistan through these lenses. This journal employs a qualitative approach with a historical method, investigating how Pakistan's formation was influenced by the revivalist movement's ideology and identity. Through historical analysis of previous journals, it is evident that the Islamic Revivalist Movement played a crucial role in Pakistan's formation. The movement's ideology, which emphasized a return to Islamic values and encouraged social-political reform, shaped a distinct national identity for Pakistan, which became a driving force in the struggle for independence and state formation.